The Encyclopedia of Christianity, Volume 1 (A-D) - Fahlbusch, Erwin,; Lochman, Jan Milič,; Mbiti, John,; Pelikan, Jaroslav,; Vischer, Lukas, (Religious Studies, Theology and Philosophy - Book Archive pre-2000., 1999)
A major intellectual resource . Jaroslav Pelikan, from the foreword. The multiple award-winning Encyclopedia of Christianity (EC), copublished by Brill and Eerdmans, is a monumental five-volume work presenting the history and current state of the Christian faith in its rich spiritual and theological diversity around the world. Volume 1 (A-D) contains 465 articles featuring - articles on all but the smallest countries of the world, including the former communist nations that have gained independence since 1989; - the latest statistical information from David B. Barrett on the religious affiliation and ecclesiastical breakdown of each country and continent; - articles on doctrines, denominations, and social and ethical issues in relation to the churches; - biographical articles on prominent figures through church history. The Encyclopedia of Christianity is also available online.